Aplicability of Efficient Microorganisms (EM) in agriculture: literature review (Research, Society and Development, 2022)
One of the challenges of the agriculture sector is the production of food in larger dimensions and with less generation of solid residues in the stages of the production chain, since these can cause serious environmental and agricultural soil damage. However, several measures can be adopted, and what would be a problem, can become a solution for the farmer. The composting technique has been an efficient alternative for the reuse of residues of both animal and vegetable origin, which, when going through the decomposition process, can be incorporated into the soil. Aiming at a greater acceleration and stabilization of these residues, the addition of Efficient Microorganisms (EMs) has been used. In addition to being used in decomposition, the MEs favor the availability of soil nutrients and minerals to plants effectively. Thus, this study conducted a bibliographic survey on Brazilian academic production, with regard to MEs. And, more specifically, categorize the different manuscripts, based on criteria such as the biological potential in agriculture and the different types of substrates, where MEs were analyzed. Based on the results found in this review, it is concluded that MEs have a wide use and benefits for the sustainable development of agriculture. It is also noticed that several researches prove its advantages in the process of substrate production through the treatment of residues with the use of composting and vermicomposting techniques, enabling their reintegration into arable soils, contributing to the improvement of their physical-chemical and biological conditions.